The Management Direction of Industrial Business Organization with the Buddhadhamma Principles - Lamsutthi, Vichai; Silpcharu, Thanin (Applied Science and Engineering Progress, 2020)
The purposes of this research were to study management direction of industrial business organization with the Buddhadhamma principles and to develop the model of management direction of industrial business organization with the Buddhadhamma principles in order that this direction would be applied in operating the industrial business to balance and lead to sustainable success. Both quantitative and qualitative methods were employed; conducting the in-depth interview with specialists and the survey from 500 entrepreneurs with good corporate governance. The results revealed that the importance level of management direction of industrial business organization with the Buddhadhamma principles was at high level. The analysis showed that the developed structure equation model passed the evaluation criteria, and was consistent with the empirical data. Its chi-square probability level, relative chi-square value, goodness of fit index, and root mean square error of approximation were 0.100, 1.089, 0.946, and 0.013 respectively.